An interesting cause of faecal occult blood. (20th August 2012) - Rabb, Nicolas; Kitsanta, Panagiota; Hunt, Lesley; Riley, Stuart
Abstract : A 69-year-old man presented to bowel cancer screening after testing for faecal occult blood. Initial colonoscopy had been limited by a sigmoid stricture and a barium enema had revealed a suspicious mass in the corresponding area. He was referred for repeat colonoscopy, which showed a hard structure crossing the mid sigmoid colon, with both ends impacted into the bowel wall. A CT scan revealed what appeared to be a small bone impacted in a diverticulum with evidence of recent inflammation and a sealed perforation. The patient had recently been managed conservatively for an episode of diverticulitis at his local hospital but was currently asymptomatic. Owing to the possibility of future complications he underwent a laparoscopic sigmoid colectomy to remove the offending foreign body.